Second Derivative Spectrophotometric Determination of Phenytoin in Pharmaceutical Preparations. - Al-Bayati, Yehya K; Karabat, Raad R (Al-Nahrain Journal of Science, 2018)
A simple, rapid, accurate, precise, specific and economical spectrophotometric method was used for determination of phenytoin .In this study, a second derivative spectrophotometric method was used for the determination of phenytoin (PHT). This method obeys Beer’s law in the employed concentration ranges of 2-10 ppm for phenytoin. The UV derivative spectra 1D for (PHT) have (V) at 233.3 nm,2D spectra for (PHT) have (P) at 226.7 nm, 3D spectra for PHT) have (P) at 223.6 nm, and (V) at 230.4 nm4D spectra for (PHT) have (P) at 236.5 nm, and (V) at 228.5nm.thelinear concentration ranges (2-10) ppm with correlation coefficient (r) 0.9996, 0.9987, 0.9973, 0.9979. The second derivative D2 tech. at (226.7) nm successfully applied for determination the Phenytoin drug in pharmaceutical samples. Results of analysis were validated statistically and by recovery studies.